Postnatal histological changes in epididymis of Madras Red ram lambs maintained under grazing and feed lot systems* - NAIDU, K VENUGOPAL; PATIABlRAMAN, S R (The Indian Journal of Animal Sciences, 2014)
The present study was made on histology in which epididymal tubules revealed columnar type of epithelium up to 4 months of age and subsequently in all the 3 regions of the epididymis pseudostratitied columnar was noticed. By seventh months of age cpididymal tubules of lambs under feeolot system showed sperms, whereas sperms were noticed in the tubules only by 8 month of age in lambs under grazing system. There were significant differences in the dia of the epididymal tubules between the regions of caput, corpus and cauda and also between age groups. At all ages, the dia of the epididymal tubules increased from caput, through corpus to cauda epididymis.